A developmental perspective on sleep consistency: Preschool age through emerging adulthood. Issue 1 (2nd January 2023) - Nicholson, Laura; Bohnert, Amy M.; Crowley, Stephanie J.
ABSTRACT: Objective/Background: Beyond sleep duration, the regularity of sleep patterns (e.g., sleep consistency), including variability in sleep timing (e.g., bedtime, wake time) and duration, is a critical marker of sleep health. Sleep consistency is captured using a variety of methods within the literature (e.g., sleep intraindividual variability, social jetlag), but most of the research focuses on adolescents. Methods: Drawing on a developmental perspective, this narrative review highlights how normative changes at the individual (e.g., biological, cognitive, and social) and contextual (e.g., home, school, sociocultural) levels may contribute to inconsistent sleep patterns across development. Results and Conclusions: This review emphasizes how inconsistent sleep may increase across pivotal transitions throughout development (e.g., elimination of naps, puberty, summertime, entering college). Finally, recommendations for measuring sleep consistency and areas to address in future research are discussed.